Kualitas Hidup Lansia dalam Perspektif Spiritualitas di Panti Wreda Adi Yuswo di Kota Semarang (International Forum of Researchers and Lecturers, 2024)
The elderly is a final condition in human life which is characterized by physiological and psychosocial changes. The elderly at the Adiyuswo Semarang Nursing Home are elderly people who are categorized as abandoned. One of the health services obtained by the elderly at the Adiyuswo Nursing Home is care that supports spirituality. Spirituality prevents the elderly from committing maladaptive actions. This research is aimed at identifying the relationship between the level of spirituality and quality of life in the elderly in the Adiyuswo Nursing Home. The research sample was 40 elderly respondents over 60 years old, the research design used cross sectional with the Stratified Random Sampling technique. Data analysis using Chi-Squre showed that there was a relationship between the level of spirituality and quality of life in the elderly (p-value = 0.000 < 0.005 and X2 = 21.774). The results of the analysis also showed an OR value of 4,745 which means that a low level of spirituality is 5 times more likely to have alow quality of life. The results of this research are expected to be beneficial for services, institutions of Nursing Homes and the development of social sciences, as well as research related to improving the quality of life by increasing the spirituality of the elderly. The purpose of this study is to find out the relationship between spiritual aspects and the level of quality of life of the elderly in the Adiyuswo Semarang Nursing Home.